FACTORS RELATED TO THE COMPLAINTS OF MUSCULOSKELETAL DISORDERS AT PT. DETPAK INDONESIA WORKERS IN 2021 - Alfaatihah, Marsya Balkhies; Suherman; Dihartawan; Herdiansyah, Dadang (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Musculoskeletal Disorders (MSDs) are a group of abnormal conditions that affect the functioning of body tissues. MSDs occur due to work factors (workload, work posture, work duration, and repetitive movements), individual factors (age, gender, years of service, smoking habits, length of work, physical fitness, and BMI), and environmental factors (temperature, vibration, and lighting) and psychosocial factors. According to the World Health Organization and data from the Global Burden of Disease, about 1.71 billion people worldwide have musculoskeletal disorders. The purpose of this research is to find out the factors related to complaints of musculoskeletal disorders in PT. Detpak Indonesia workers in 2021. Cross-sectional study design, primary data was distributed through questionnaires, and the number of respondents was 97 employees of the accidental sampling technique. This data analysis used the chi-square statistical test (α = 0.05). Variables related to complaints of musculoskeletal disorders are physical fitness (p value = 0.021 and OR = 7.238), years of service (p value = 0.019 and OR = 3.947), length of work (p value = 0.001 and OR = 6.979) and work posture ( p value = 0.011 and OR = 4.340) while the unrelated variable is gender (p value = 0.147 and OR = 2.514). From this study that there is a relationship between physical fitness, working period, length of work, and work posture with complaints of musculoskeletal disorders in workers. This study suggests that workers stretch before and after work, work interspersed with breaks if workers feel tired, and more pay attention to work position when doing work.